Evolutionary biogeography of South American weevils of the tribe Naupactini (Coleoptera: Curculionidae) - del Rio, Maria Guadalupe (2015)
Aim: Naupactini are highly diverse weevils, widespread in the Neotropical region. Their evolution may have been driven by geological and environmental changes. Our main goals were to explain the biotic diversification of this tribe in South America and to test previous hypotheses on the relationships between distribution areas. Location: Neotropical South America. Methods: We compiled geographical records for 165 species of South American Naupactini. We then applied a track analysis and a parsimony analysis of paralogy-free subtrees to obtain generalized tracks and a general area cladogram, respectively. Results: We retrieved 11 generalized tracks that coincided broadly with biogeographical areas of Neotropical South America: Northern Venezuelan, Galápagos Islands, Ecuadorian, Yungas, Cerrado, Caatinga, Puna+Pacific coastal deserts, Chacoan, Atlantic+Parana forests, Monte and Pampean. The single general area cladogram obtained showed the following topology: ((Northern Venezuelan-Ecuadorian) (Galápagos Islands-Puna+Pacific coastal deserts) (Yungas (Cerrado (Monte (Pampean (Chacoan-Atlantic+Parana forests)))))). Main conclusions: The general patterns identified agree with biogeographical provinces of modern regionalizations, assumed to have been caused by vicariance. These biogeographical units form two main components, one from north-western South America and the other from south-eastern South America, separated by the barrier of the Andean cordillera. The absence of other discernible geological barriers and the influence of the Plio-Pleistocene cycles make it difficult to elucidate the historical relationships between most forest areas and nearby open areas of South America. These observations indicate that the taxa under consideration underwent dispersal at different times, contributing to complex biogeographical patterns.